Attaining the high-energy orbit of nonlinear energy harvesters by load perturbation. (15th July 2019) - Wang, Jiahua; Liao, Wei-Hsin
Graphical abstract: Highlights: Electrical load effects are studied for nonlinear energy harvesters. The load perturbation method is firstly used to attain the high-energy orbit. The proposed method is simple to implement while consuming little energy. Simulation and experiments reveal the power output achieves multifold augmentation. Abstract: Energy harvesters, especially nonlinear systems with broad bandwidth, have made it possible for devices in IoT (Internet of Things) to extract energy from the ambient environment. However, due to the multistability feature of the nonlinear system, high and low energy orbits coexist in the system. It is critical to control the multistability so as to obtain high energy output. This paper proposes the load perturbation method to attain the high-energy orbit of nonlinear energy harvesters. Based on the electromechanical model, investigating the electrical load effects on the system shows that varying load results in different system states, which suggests that the load perturbation may trigger the transformation of system states. Therefore, a load perturbation by disconnecting the electrical load is employed to attain the high-energy orbit. Simulation and experiments reveal that the load perturbation can stimulate high-energy orbit oscillation for both monostable and bistable systems. The power output can be amplified for multifold times. The perturbation requires only one switch without additional mechanical structures. Furthermore, this method consumes little energy so that no external electrical energy source is needed. The load perturbation method opens opportunities for wide applications of nonlinear energy harvesters.